PEDAGOGICAL EFFECTS OF MODERN EDUCATIONAL METHODS - Yurchenko, Valeriia (Collection of scientific papers «ΛΌГOΣ», 2022)
Nowadays modern methods of teaching foreign languages are numerous and very popular in many countries of the world. Their educational effect is well-known, but it is often ignored that most of them also have a certain pedagogical effect and can be used to influence students’ behavior. This work aims at classifying different teaching methods according to their pedagogical effect and offering some recommendations for their practical use.